PROLACTIN AND RECEPTOR GENE POLYMORPHISM AND THEIR ASSOCIATION WITH SOME PRODUCTIVE TRAITS OF HOLSTEIN COWS - R. H. Al-Obaidi,; H. R. A. Al-Janabi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted at Al-Khalis Dairy Cattle Station in Diyala Governorate during the productive season during 2021–2022. 63 Holstein cows were selected randomly to study the effect of prolactin gene (PRL) and prolactin gene receptor (PRLR) polymorphism on milk production, milk components, and reproductive traits in Holstein dairy cows. The results showed three SNPs of PRL gene (TT, TC, and CC). There are highly significant differences (P>0.01) between the percentages of the genotypes, which reached (79.37, 17.46, and 3.17% , respectively ) and three SNPs for PRLR gene ( TT , TA and AA with percentage  47.62 , 41.27 and 11.11 respectively) in Holstein dairy cows in Iraq. the results showed there were a significant effect of TC genotype (4187.82 kg) of total milk yield compared with TT (4013.02 kg ) and CC (3505.00 kg) The polymorphism for PRL gene The total milk production was higher in TA genotype (4321.04 kg) followed than TT genotype (4025.53 kg) and AA genotype (2877.33 kg) for PRLR gene. The polymorphism of the PRL and PRLR genes did not significantly effects on the reproductive traits and milk components except for fat percentage in the PRL gene and lactose percentage in the PRLR gene. It can be concluded, a highly significant relationship between the prolactin gene and the prolactin receptor gene with milk production, so it can be used for genetic improvement of milk cows.